Non-coding RNAs targeting NF-κB pathways in aquatic animals: A review - Zhao, Tanjun; Zou, Yang; Yan, Hanyu; Chang, Yaqing; Zhan, Yaoyao (Frontiers in Immunology, 2023)
Nuclear factor-kappa B (NF-κB) pathways have a close relationship with many diseases, especially in terms of the regulation of inflammation and the immune response. Non-coding RNAs (ncRNAs) are a heterogeneous subset of endogenous RNAs that directly affect cellular function in the absence of proteins or peptide products; these include microRNAs (miRNAs), long noncoding RNAs (lncRNAs), circular RNAs (circRNAs), etc. Studies on the roles of ncRNAs in targeting the NF-κB pathways in aquatic animals are scarce. A few research studies have confirmed detailed regulatory mechanisms among ncRNAs and the NF-κB pathways in aquatic animals. This comprehensive review is presented concerning ncRNAs targeting the NF-κB pathway in aquatic animals and provides new insights into NF-κB pathways regulatory mechanisms of aquatic animals. The review discusses new possibilities for developing non-coding-RNA-based antiviral applications in fisheries.